KESENJANGAN INFRASTRUKTUR DIGITAL DI LEMBAGA PENDIDIKAN ISLAM: STUDI KOMPARASI PESANTREN PERKOTAAN DAN PEDESAAN - Hoerul Umam; Muhammad Beryl Walida Askari; Diki Sulaiman (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The acceleration of digitalization in the Islamic education system today faces a serious challenge in the form of sharp disparities in infrastructure between regions. This research aims to analyze the technological gap between urban and rural pesantren and its impact on modern learning governance patterns. Through a qualitative method with a descriptive comparative study approach, the data collection process relies on a triangulation scheme involving observation of physical facilities, documentary study, and semi-structured interviews. The investigation results prove that urban pesantren have been able to adopt interactive Learning Management System (LMS) platforms thanks to the stability of fiber optic connections. Conversely, rural pesantren still rely on emergency instant messaging media due to high cellular network latency and a low hardware ratio. Fiscal constraints and the limited information technology (IT) capacity of teachers in rural areas exacerbate this inequality. This study concludes that the integration of teacher digital upskilling programs and sustainable infrastructure subsidies is an absolute key to equalizing the quality of graduates from Islamic educational institutions.